COVID-19 induced challenges in refugee management: lessons learned from Rohingya camps in Bangladesh - Bulbul Siddiqi; Nur Newaz Khan (Frontiers in Human Dynamics)
Bangladesh's Rohingya crisis is more complex than ever due to several factors. Failure to repatriate Rohingya refugees to their homeland, declining sympathy among the host communities, funding reductions from the international communities, the 2021 military coup in Myanmar and the recent war between the Arakan Army and Myanmar military are the key factors behind such complexity. In addition to all these difficulties, COVID-19 created new barriers and left its mark on this ongoing crisis, which has created further vulnerabilities among the mass population of Rohingya living in Bangladesh. Reduced job opportunities, failure to address increasing internal conflicts, and restricted mobility of the various aid workers during COVID-19 have made the situation worse for the Rohingya. Based on qualitative research among the Rohingya and the humanitarian workers in the Rohingya camps, the paper argues that COVID-19 puts the life and future of the Rohingya at further vulnerability. We conducted a total of 30 interviews, 15 with the Rohingya community and 15 with the humanitarian actors working on the ground. The impact of many such vulnerabilities is still visible in the Rohingya refugees and has created prolonged difficulties in managing the Rohingya in the camps.